2018
DOI: 10.1155/2018/5806037
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Lumbar Interbody Fusion: Technical Note and Preliminary Clinical Experience with 2-Year Follow-Up

Abstract: Objective Endoscopic surgeries have been attempted in the field of lumbar decompression and fusion surgery in the past decade. Percutaneous endoscopic lumbar interbody fusion (PELIF) is a new-emerging technique taking advantages of an anatomical (Kambin's triangle) to achieve simultaneous decompression and fusion under endoscopic visualization. The purpose of this study is to evaluate the feasibility and safety of PELIF technique with general anesthesia and neuromonitoring. Methods The authors present the deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 24 publications
(46 reference statements)
3
57
1
Order By: Relevance
“…Nerve root injury is one of the most serious complications of spinal surgery, so to protect nerve roots, we must pay great attention before each step in the procedure that may result in damage. Foraminoplasty is a necessary step for enlarging the foramen in order to provide su cient space for subsequent procedures and eliminate exiting root injury [19]. Similar to the PELD technique, the nerve root can be protected by a working tube with a beveled tip from trepan cutting and cage implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nerve root injury is one of the most serious complications of spinal surgery, so to protect nerve roots, we must pay great attention before each step in the procedure that may result in damage. Foraminoplasty is a necessary step for enlarging the foramen in order to provide su cient space for subsequent procedures and eliminate exiting root injury [19]. Similar to the PELD technique, the nerve root can be protected by a working tube with a beveled tip from trepan cutting and cage implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the percutaneous endoscopic transforaminal lumbar interbody fusion (Endo-TLIF) technique was reported to address a variety of spinal disorders by using endoscopic and expandable cages through Kambin's triangle [19,20]. Endo-TLIF technique was derived from the percutaneous endoscopic lumbar discectomy (PELD) technique and combined endoscopic visualization, expandable cage technology, and interbody fusion technique [21].…”
Section: Introductionmentioning
confidence: 99%
“…And then, Jacquot et al demonstrated that the complication rate was up to 36% via endoscopic lumbar interbody fusion, and they believed that technical improvements were necessary [12]. After that, in order to decrease the complication rate, several researchers began to design and improve the endoscopic lumbar interbody fusion and related surgical instruments [11][12][13][14][15][16][17][18][19]. Most of studies showed that the endoscopic lumbar fusion technique could be a promising treatment for lumbar degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Jacquot et al believed that it was necessary to make decisive technical improvements to decrease the complication rate via endoscopic fusion surgeries [12]. With the advancement of endoscopic fusion techniques, some researchers have reported satisfactory outcomes through endoscopic surgery, but the learning curve of these techniques was relatively long [14,15]. Hence, we developed a percutaneous endoscopic transforaminal lumbar interbody fusion (PE-TLIF) technique.…”
Section: Introductionmentioning
confidence: 99%
“…More oblique access to the disc could allow for adequate neural decompression and insertion of a cage with removal of less than 50% of the facet bone [11]. Wu J et al [12] were the rst to perform a traditional PELD procedure. After primary disc removal and nerve root decompression, the working tube was withdrawn, replaced with a working tube (15 or 18 mm in diameter), and an autogenous bone graft from the superior articular process and a commercially available cancellous bone allograft was placed into the interbody space.…”
Section: Discussionmentioning
confidence: 99%